PERANCANGAN SISTEM E-CRM PROVIDER INTERNET PADA CV. AHYEIN PRATAMA MANDIRI AIR JOMAN - Irfan Hakim Nasution; Fauriatun Helmiah; Sudarmin . (Jurnal Teknologi Informasi dan Pendidikan, 2022)
CV. Ahyein Pratama Mandiri Air Joman is a company engaged in the field of providing internet services (internet service provider), whose head office is on Jl. Binjai Serbangan Protocol, Air Joman District. A company that was founded in 2017. At this time CV. Ahyein Pratama Mandiri Air Joman does this by waiting for customers to come to the office or customers providing information about places, privileges and products to other potential customers. Inadequate reporting of customer complaints makes it difficult to know the level of customer satisfaction so that with marketing like this, the opportunity to get potential customers to the maximum is not fulfilled and this is very unfortunate given the increasing number of internet network products. Dissemination of information that is not neat makes it difficult for customers to know the latest information, thus influencing customers to switch to other providers. CV. Ahyein Pratama Mandiri Air Joman built a system using CRM (Customer Relationship Management), where this system is expected to facilitate CV. Ahyein Pratama Mandiri Air Joman in managing services for customer satisfaction. So that customers remain loyal and on the other hand also get new customers from time to time.